Trickle down this effect: negotiations of culture, care, and freedom in contemporary Cairo international schools - Caldwell, Anne (AUC Knowledge Fountain, 2012)
This thesis attempts to analyze the contradictions and practices of a neoliberal ethical project among a privileged class in contemporary Cairo. The growing presence and availability of international schools in Cairo has reconfigured particular aspects of culture, care, and freedom for elite subjects over the past forty years. The main research question is: how are globalized notions of well being, self-realization, and personal fulfillment transmitted through the work of neoliberal discourse and staff at international schools in Cairo. It has been identified in this thesis that certain forms of care and responsibility are tightly bound and shaped by a neoliberal project that emphasizes freedom and entrepreneurship. As these forms of self-fashioning and self-making are globally circulated through the work of international schools in Cairo, they further convolute meanings of "the good life" and striving toward its end which can often result in particular forms of suffering and shifting imaginations of relating to one's self. This paper has reviewed literature on the subject and accumulated a more thorough understanding from several interviews with teachers and counselors at international schools in Cairo as well as from surveying students at an international university in Cairo to show the ways in which privilege can too disenfranchise much like failed neoliberal policies in contemporary society.